2016
DOI: 10.1021/acs.macromol.6b00502
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Diverse Poly(thienylene vinylene)s (PTVs) with Systematically Tunable Properties through Acyclic Diene Metathesis (ADMET) and Postpolymerization Modification

Abstract: Poly­(thienylene vinylene)­s (PTVs) are a unique class of low bandgap conjugated polymers that have received relatively little attention in organic electronic applications due to the limitations in conventional synthetic methodologies that are not capable to produce PTV structures beyond the rudimentary forms. We report here facile synthetic methods, combining acyclic diene metathesis (ADMET) and postpolymerization modification reactions, toward a series of structurally diverse PTVs. Specifically, halogen subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…[10][11][12] It was however surprising to note that investigations on the reductive coupling between aryl and vinyl electrophiles are exceptionally rare, [13][14][15][16] although vinyl arenes are as ocalled privileged scaffold found in bioactive natural products, pharmaceuticals,a nd polymers. [17] An example known in the literature emphasizes as trategy involving cobalt catalysis. [13,14] However,t his method is constrained to very limited vinyl substrates.D ropwise addition of vinyl halides to 2equivalents of an aryl bromide was key to avoiding the dimerization of individual halides (Scheme 1).…”
mentioning
confidence: 99%
“…[10][11][12] It was however surprising to note that investigations on the reductive coupling between aryl and vinyl electrophiles are exceptionally rare, [13][14][15][16] although vinyl arenes are as ocalled privileged scaffold found in bioactive natural products, pharmaceuticals,a nd polymers. [17] An example known in the literature emphasizes as trategy involving cobalt catalysis. [13,14] However,t his method is constrained to very limited vinyl substrates.D ropwise addition of vinyl halides to 2equivalents of an aryl bromide was key to avoiding the dimerization of individual halides (Scheme 1).…”
mentioning
confidence: 99%
“…This methodology therefore afforded synthesis of defect free, high molecular weight, all trans poly(9,9-di-n-octyl-fluorene-2,7-vinylene) (PFV) [30], poly(2,5-dialkyl-pheny-lene-1,4-vinylene)s (PPVs) [31], and poly(N-alkylcarbazole-2,7-vinylene)s (PCVs) [32], poly(thienylene vinylene)s [34]- [40] by using Schrock type molybdenum-alkylidene, and ruthenium-carbene catalysts (Scheme 6). The resultant polymers [30] [31] [32] possess high stereo-regularity (all trans olefinic double bond) and analytically pure (defect-free), and showed unique photophysical properties compared with polymers prepared by other methods.…”
Section: Introduction: Backgroundmentioning
confidence: 99%
“…Synthesis of poly(thienylene vinylene) by ADMET polymerization using Ru-carbene catalysts [34]- [40].…”
Section: Introduction Of End Functionality Into Conjugated Polymers Bmentioning
confidence: 99%
“…5,[17][18][19][20] Poly(thienylenevinylene)s (PTVs), which is one of polythiophene derivatives (PTs) containing alternating thiophene and vinylene units along the main-chains, have been intensively studied for their photoelectrical property and photovoltaic applications, due to their good charge transport property. 2,[21][22][23][24][25] In addition, previous literatures also have shown that polythiophene derivatives (PTs) with thienylene-vinylene conjugated side chains possess broader absorption spectra and relatively low-lying HOMO energy levels compared with their linear analogues, since the thienylene-vinylene conjugated side chains could extend the p-electron delocalization of polymer backbone. 2,[26][27][28][29][30] For example, chemically graing conjugated side chains onto polymer backbone through vinylene-linkage, such as thienylene-vinylene 31 and bi(thienylenevinylene), 11 is effective to extend the absorption range and down-shi the HOMO energy level of polythiophene.…”
Section: Introductionmentioning
confidence: 99%